INFLUENCE OF THE SOCIAL ENVIRONMENT ON DEVELOPMENT OF CREATIVE POTENTIAL IN YOUNGER SCHOOLCHILDREN - Khamidova Gulbahor (American Journals, 2023)
The article reveals the importance of social environment in development of creative potential in younger schoolchildren. The subject-subject relations between adults and children in the course of creative activity are analyzed not only from the point of degree of influence of social environment on creative abilities, but also from the point of its importance.
Keywords: A creative person, creative potential, social environment, younger schoolchildren.